2012
DOI: 10.1089/ars.2011.4013
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation of the GeneNCF1Is Associated with Rheumatoid Arthritis

Abstract: These data suggest that an increased copy number of NCF1 can be protective against developing RA and add support to previous findings of a role of NCF1 and the phagocyte NADPH oxidase complex in RA pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 39 publications
7
76
0
Order By: Relevance
“…In addition, p47 phox (encoded by NCF1) has been genetically linked with rheumatoid arthritis through genetic association as well as animal model studies. 29,43 In addition, the H389Q coding variant of p67 phox (encoded by NCF2), also identified in this study, was recently associated with systemic lupus erythematosus. 30 These studies suggest that mutations in NOX2 results in immunodeficiency (CGD or MSMD), and functional variants in other components of the NADPH oxidase complex contribute to susceptibility to immune-related diseases, including a significant role in the development of VEOIBD in a large cohort.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, p47 phox (encoded by NCF1) has been genetically linked with rheumatoid arthritis through genetic association as well as animal model studies. 29,43 In addition, the H389Q coding variant of p67 phox (encoded by NCF2), also identified in this study, was recently associated with systemic lupus erythematosus. 30 These studies suggest that mutations in NOX2 results in immunodeficiency (CGD or MSMD), and functional variants in other components of the NADPH oxidase complex contribute to susceptibility to immune-related diseases, including a significant role in the development of VEOIBD in a large cohort.…”
Section: Discussionsupporting
confidence: 57%
“…This included a coding R90H p47 phox variant (encoded by NCF1; rs3447) that was previously shown by Olsson et al in rheumatoid arthritis patients to significantly decrease reactive oxygen species (ROS) production. 29 In addition, an NCF2 SNP (rs17849502) resulting in a p67 phox H389Q variant previously associated with systemic lupus erythematosus, 30 was found in 14 VEOIBD patients. This p67 phox H389Q variant was previously shown to reduce ROS production and was suggested to reduce p67 phox binding to VAV1, an important process for FcyR-dependent ROS production.…”
Section: Targeted Exome Sequencingmentioning
confidence: 95%
“…The results were interpreted as consistent with the view that both multiple genes and also sex differences contribute to disease progression in different subsets of rheumatoid arthritis patients. A separate study by the same group reported a decreased risk of rheumatoid arthritis associated with increased copy number of NCF1 (p47phox) (206). NCF4 has also been associated with Crohn's disease (239).…”
Section: Human Disease Associations With Polymorphisms In Nox2 and Phmentioning
confidence: 96%
“…106 Furthermore, an increased copy number of Ncf1 can be a protecting factor, as RA patients are prone to have lower copy number of Ncf1 compared to healthy controls. 107 Reduction of ROS by dietary intake of antioxidants seems to have an influence on arthritis incidence, too. A study showed a correlation between a high consumption of vitamin C or vitamin E by women and the occurrence of RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%